Translating sarcasm and repulsion, or the discredited bourgeois by Michel Provins - Kaczmarek, Tomasz (Traduttologia e Traduzioni, vol. III: Interdisciplinarietà della traduzione, 2021)
In this article, the author examines the translation of Michel Provins' theater play, entitled Degenerates! from French into Polish. The extracts of this extensive drama have been published in the anarchist journals, because the playwright is mercilessly denouncing the flaws of the bourgeoisie. The latter, instead of being an example for the whole nation, lives shamefully on the hooks of the oppressed people. This text, written almost 120 years ago, has not lost any relevance because it castigates abuses of power. The mood and the grotesque are at the rendezvous. The translator shows the strategies of his work, his design was to keep as much as possible the originality of the style of Provins while respecting the criteria of the theatrical translation.